Systematics and biogeography of Marsikomerus Attems, 1938, a misunderstood genus of centipedes (Geophilomorpha: Schendylidae) - Hoffman, Richard (1991)
Marsikomerus (Attems 1938) is transferred from Geophilidae to Schendylidae, and shown to be a senior synonym of Simoporus (Chamberlin 1940) and Lanonyx (Chamberlin 1953). The type species M. pacificus is redescribed and illustrated in detail from the holotype; similar but less extensive treatment is provided for M. lanaius and M. texanus. The value of some traditionally used characters and the distribution of the genus (Hawaii, southwestern United States, northern Mexico) are discussed.